6 Prevalence and CMR characteristics of apical HCM. (18th April 2016) - De Garate, E; Dastidar, A Ghosh; Singhal, P; Venuti, G; Amadu, A; Baritussio, A; Scatteia, A; Lawton, C; Rodrigues, J; Bucciarelli-Ducci, C
Abstract : Hypertrophic cardiomyopathy (HCM) is the most common cause of sudden cardiac death in young adults. The 3 main phenotypes are asymmetric (most common), concentric and apical. Literature suggests apical HCM is rare and more benign, but data is scarce. We sought to describe prevalence and characteristics of apical HCM in a large CMR service. Methods: We reviewed 3, 100 scans (Jan 2014–Mar 2015). Protocol included cines, early and late gadolinium enhancement imaging. 114 consecutive HCM patients were identified. Asymmetric HCM defined as septal/ free wall thickness ratio > 1.3; apical HCM as apical wall thickness > 15mm or apical/basal wall thicknesses ≥ 1.3–1.5. Concentric HCM defined as symmetrical hypertrophy of ventricular wall without regional preferences. Non-apical HCM (asymmetric and concentric phenotypes) were compared with apical HCM. Fisher's exact t-test and unpaired t-test were performed for statistical significance (P-value < 0.05, statistically significant). Univariate and multivariate logistic regression analyses were performed to determine CMR predictors of apical HCM. Results: 10 patients were excluded, leaving 104 patients, median age 60years; 70% male. 70% had non-apical HCM (5 patients concentric HCM, the rest asymmetric HCM) and 30% apical HCM. Mean maximum LV wall thickness, indexed LV mass, stroke volume, prevalence of LVOTO and SAM were greater in non-apical group. Presence of LGE was high in both groups (>85%) and wasn't statistically different. Univariate predictors of apical HCM included maximum LV wall thickness, indexed stroke volume, LVOT obstruction (Table 1 ). In the multivariate model, maximum wall thickness remained the only significant predictor. Conclusions: Our study suggests that prevalence of apical HCM is almost 1/3rd of all observed cases. It also demonstrates that prevalence of LGE was high in apical HCM, suggesting that better prognosis of apical HCM based on the absence of myocardial fibrosis, should be reconsidered. Further large trials are needed to better understand the pathophysiology.